Sleep Quality And Obesity: A Community Based Cross-Sectional Study - Bishal Joshi; Jay Prakash Jha; Aishwarya Gupta; Srijana Rayamajhi; Sudeep Kumar Yadav; Laxmi Shrestha; Ajit Pahari; Preetu Gurung (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Obesity and poor sleep quality are challenging public health issues worldwide. Despite numerous research connecting obesity and sleep quality, there is limited study on it at speciﬁc community settings like Lumbini Province, Nepal. So, this comprehensive community-based cross-sectional study was conducted with the aim to assess the relationship between sleep quality, and obesity. MATERIAL AND METHODS This study was conducted from April to August 2023 in Ranigaun-2, Bhairahawa, Nepal. Total 76 participants were enrolled in the study and data were collected through door-to-door visits and included socio-demographic information, body-mass index (BMI), waist-hip ratio (WHR), and sleep quality assessed using the Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics, Pearson’s correlation, and logistic regressions were used for analysis. RESULTS The study included 35 males and 41 females with a mean age of 36.88±10.06 years. The mean BMI was 25.95 ± 3.78 kg/m² and average waist-hip ratio was 0.9 ± 0.06. The mean PSQI score was 6.82 ± 3.24, indicating poor sleep quality in about 60% of participants. No signiﬁcant correlation was found between BMI, WHR, and sleep parameters. Age was directly correlated with sleep latency and PSQI score, and inversely with sleep efﬁciency. CONCLUSION Poor sleep quality was prevalent in the community, but no signiﬁcant association was found between sleep indices and obesity parameters. The study found the impact of age on quality of sleep, highlighting the importance demographic factors in sleep research. In future, longitudinal studies are needed to explore the relationship between sleep, overweight, and obesity.